Review of Teacher development for immersion and content-based instruction; Editors: Laurent Cammarata, T.J. Ó Ceallaigh; Publisher: John Benjamins Publishing Company, 2018; ISBN: 97890272074877; Pages: 201 - Papaja, Katarzyna Lidia (Studies in Second Language Learning and Teaching, 2021)
Searching for ways to expand the spectrum of methods of teaching and learning foreign languages triggers valuable initiatives and offers support for both students and teachers. Programs such as French immersion in Canada, content-based instruction (CBI), and content and language integrated learning (CLIL) have become popular across the world (Harrop, 2012), which is rapidly becoming a global village where the role of languages is crucial. In an integrated world, teaching content through language is viewed as a modern form of educational delivery; therefore, as the editors emphasize “teacher preparation and professional development endeavors are key drivers of successful I/B and CBI programs across a variety of models” (p. 3). Teacher Development for Immersion and Content-Based Instruction is a key contribution to the field, which offers valuable insights into the complexity of teacher preparation as well as further professional development in the case of immersion/bilingual contexts.